Teaching Chinese Language in Singapore Retrospect and Challenges - Soh, Kaycheng (Springer Nature Singapore : Imprint: Springer, 2016)
This collection of articles begins with an overview of the Reviews from past decades, then goes on to describe the current practices, and foretells the possible future developments. This is followed by a discussion of the use of ICT and surveys on several professional aspects of teaching, including teachers' training needs and perception of student difficulties, assessment literacy, familiarity and use of language teaching strategies, as well as perceived social status and job satisfaction. The book ends with an extensive discussion of bilingualism and code-switching as well as the teaching of Chinese culture in Singapore schools. The comprehensive coverage provides a milestone in Chinese Language teaching in the multi-lingual context of Singapore.